REMOVING BORON FROM METALLURGICAL GRADE SILICON BY A HIGH BASIC SLAG REFINING TECHNIQUE - Wu, Jijun; Xu, Min; Liu, Kai; Ma, Wenhui; Yang, Bin; Dai, Yongnian (Journal of Mining and Metallurgy, Section B: Metallurgy, 2014)
A new purification method of removing boron from metallurgical grade silicon (MG-Si) using a high baisicity slag was developed in this paper. The typical impurities Al, Ca, Ti, B, P etc in MG-Si can be removed by the binary calcium sillicate slag and it is especially efficient for removing impurity Boron. It was found that the maximal distribution coefficient of boron between calcium sillicate slag and silicon reaches to 1.57 when the mass ratio of CaO/SiO2 was 1.5 and the composition was 60%CaO-40%SiO2. It showed that the oxidizability of calcium sillicate slag was affected and restricted by the basicity and the mass ratio of acid oxide SiO2 in slag according to the thermodynamic relationship. The boron concentration in MG-Si can be reduced from 18×10-6 to 4.5×10-6 and 1.4×10-6, respectively, when using the ternary slags 40.5%CaO-49.5%SiO2-10%Li2O and 32CaO-38%SiO2-30%Li2O.